A game against natural selection? Hibernation of migratory bat species in their summering range in Eastern Ukraine - Zagorodniuk, I. (Theriologia Ukrainica, 2018)
A series of new findings of migratory bat species that in recent years formed wintering groups in the region are described. Bats were found in buildings within human settlements in all cases. Descriptions of new autumn and winter records of Nyctalus noctula in Gorlovka and Rubizhne, Vespertilio murinus in Luhansk, Alchevsk and Donetsk, and Pipistrellus cf. pygmaeus in Mariupol are presented. These findings are considered as further evidence of formation synanthropic bat communities in eastern Ukraine and expand the geographical boundaries of the known wintering range of these migratory species within Ukraine. Similar cases are rare so far, although they indicate new changes that may soon become regular. Cases of wintering are considered as “trial of forces” of a part of the population in the context of trading-off the “cost of migration” for the “cost of hibernation” under conditions of global warming as well as of improving wintering conditions in the region due to various artificial shelters, mainly in cities.